Sludge dewatering composite conditioner and preparation method thereof
By leveraging the synergistic effects of Lewis acid metal salts, free radical generators, surfactants, and nanoparticle additives, the problems of low dewatering efficiency and poor filtrate quality in high-viscosity and high-oil-content sludge are solved, achieving low-energy and high-efficiency sludge treatment.
Patent Information
- Application Number
- CN202510041418.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Existing sludge conditioners have low dewatering efficiency when treating high-viscosity and high-oil-content sludge, cannot effectively release bound water and colloidal water, and produce poor filtrate quality, resulting in high energy consumption of mechanical equipment and increased treatment costs.
By employing the synergistic effects of Lewis acid metal salts, free radical generators, surfactants, and nanoparticle additives, the dewatering efficiency and filtrate quality are improved by disrupting the polar bonds on the surface of sludge particles, oxidatively degrading the organic colloidal layer, and forming a hydrophobic barrier, combined with physical flocculation and chemical modification.
It significantly reduces the moisture content of sludge after dewatering, reduces energy consumption for mechanical dewatering, improves the economy and efficiency of sludge treatment, and improves the quality of filtrate.
Smart Images

Figure BDA0005237075320000151 
Figure BDA0005237075320000171 
Figure BDA0005237075320000191
Abstract
Description
Technical Field
[0001] This invention relates to the field of sludge treatment technology, specifically to a sludge dewatering composite conditioner and its preparation method. Background Technology
[0002] Sludge is a major byproduct of urban wastewater treatment, typically with a high water content of 80% to 98%. The water in sludge exists in complex forms, including free water, bound water, and colloidal water. Mechanical dewatering processes mainly rely on external force to remove free water, but their ability to remove bound and colloidal water is insufficient. This results in the sludge after mechanical dewatering still maintaining a high water content, making it difficult to meet the needs of subsequent treatment and resource utilization. Therefore, the use of chemical conditioners has become a core auxiliary measure for mechanical dewatering. Conditioners can release some water by disrupting the stability and structure between sludge particles. However, existing chemical conditioners have limited effectiveness and cannot achieve low-energy, high-efficiency dewatering.
[0003] Currently widely used sludge conditioners include cationic polyacrylamide (CPAM) and inorganic salts such as aluminum and iron salts. As a flocculant, polyacrylamide promotes particle aggregation through charge neutralization, while inorganic salts reduce electrostatic repulsion on sludge particle surfaces through destabilization. These conditioners primarily function through physical flocculation between particles. However, the release of strongly bound water in sludge involves hydrogen bonding between polar groups on sludge particle surfaces and water molecules, and existing conditioners have limited effectiveness against this chemically bound water. Therefore, even with the use of conditioners, the moisture content of dewatered sludge is generally still higher than 60%, far from meeting the requirements for deep dewatering.
[0004] The composition and characteristics of sludge vary significantly depending on its source. High-viscosity sludge and high-oil-content sludge, due to the organic matter or oil layer covering the particle surface, exhibit strong hydrophilicity and high particle stability, further increasing the difficulty of dewatering. Traditional conditioning agents are insufficiently adaptable to high-viscosity, high-oil-content sludge, lacking the ability to alter the surface chemical properties of particles and disrupt colloidal stability, resulting in low dewatering efficiency. Especially in high-oil-content sludge, the oil forms a stable hydrophobic coating layer with the particles, making it difficult to effectively release bound water and colloidal water between particles. Conventional conditioning methods are inadequate for treating this type of sludge.
[0005] Existing conditioners typically rely on a single mechanism of action, such as charge neutralization or mechanical flocculation, failing to achieve synergistic effects across multiple mechanisms. This limitation is evident in the destabilization of sludge particles and water release, with limited flocculation effects and no effective alteration of particle surface hydrophilicity, resulting in low dewatering efficiency. Furthermore, conditioners are inadequate in optimizing filtrate quality; a large amount of fine particles and organic matter enters the filtrate during dewatering, increasing the difficulty and cost of filtrate treatment.
[0006] Meanwhile, to compensate for the shortcomings of conditioners, existing technologies typically require increasing the dosage of conditioners or increasing the operating pressure of mechanical equipment. This not only increases processing costs but also places higher demands on the performance of mechanical equipment, further increasing energy consumption. Furthermore, the uneven distribution of conditioner components in sludge also limits their utilization efficiency, with some conditioners being wasted during the reaction process and failing to fully exert their effects. Therefore, in the field of sludge treatment, there is still a need for a highly efficient conditioner with synergistic effects across multiple mechanisms. This conditioner should be able to target the polar chemical bonds and structural characteristics of sludge particles, combining physical flocculation, chemical modification, and surface modification to improve dewatering efficiency, reduce energy consumption, and improve filtrate quality, thereby providing a solution for the efficient treatment of sludge. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a sludge dewatering composite conditioner and its preparation method. In particular, it is a multifunctional composite conditioner designed for different types of sludge, such as municipal sludge, industrial sludge, and high-oil-content sludge. Through the synergistic effect of multiple mechanisms, including chemical modification, physical flocculation, and surface modification, it effectively improves sludge dewatering efficiency, reduces the moisture content of dewatered sludge, and improves the quality of filtrate, providing an efficient and economical solution for sludge treatment.
[0008] To achieve the above objectives, the present invention provides the following technical solution: a sludge dewatering composite conditioner and its preparation method, comprising the following components:
[0009] Lewis acid metal salts;
[0010] Free radical generating agent;
[0011] Surfactants;
[0012] Polymer-type flocculants;
[0013] Nanoparticle additives;
[0014] pH adjuster.
[0015] Preferably, the Lewis acid metal salt is a titanate or vanadate, specifically at least one of titanium tetrachloride, sodium metavanadate, and sodium metamolybdate.
[0016] Preferably, the free radical generating agent is a persulfate, specifically at least one of sodium persulfate and ammonium persulfate.
[0017] Preferably, the surfactant is an amphoteric surfactant, specifically sulfobetaine or alkylobetaine.
[0018] Preferably, the polymeric flocculant is cationic polyacrylamide.
[0019] Preferably, the nanoparticle additive is zinc oxide or titanium dioxide nanoparticles with a particle size of 10 nm to 100 nm.
[0020] Preferably, the pH adjuster is sodium hydroxide or sodium carbonate.
[0021] A method for preparing a sludge dewatering composite conditioner includes the following steps:
[0022] Lewis acid metal salts were dissolved in deionized water and the pH was adjusted to obtain Lewis acid active solutions;
[0023] A free radical generating agent is dissolved in deionized water to obtain a free radical solution;
[0024] A surfactant solution is prepared by dissolving the surfactant in deionized water.
[0025] The nanoparticle additives were dispersed in deionized water by ultrasonication to obtain a nanoparticle additive suspension.
[0026] Lewis acid active liquid, free radical solution, surfactant solution, nanoparticle auxiliary agent suspension and flocculant are mixed sequentially in proportion and stirred evenly to prepare sludge dewatering composite conditioner.
[0027] Preferably, the concentration of the Lewis acid metal salt is 20% to 40%, and the pH adjustment range is 6.5 to 7.5.
[0028] Preferably, the nanoparticle additive is dispersed by ultrasonication at a power of 100W to 200W, a frequency of 20kHz to 40kHz, and an ultrasonication time of 10 minutes to 20 minutes.
[0029] This invention provides a sludge dewatering composite conditioner and its preparation method. It has the following beneficial effects:
[0030] 1. This invention employs a technical solution combining Lewis acid metal salts and free radical generating agents. It utilizes the coordination effect of Lewis acids to disrupt the polar bonds on the surface of sludge particles, enabling free radical oxidation and degradation of the organic structure, releasing strongly bound water and colloidal water. Compared to existing conditioning methods that rely solely on flocculants or inorganic salts, this invention avoids the limitations of treatment effectiveness being affected by the complexity of sludge composition and solves the problem of difficult removal of bound water from sludge particles.
[0031] 2. This invention introduces amphoteric surfactants and nanoparticle additives to dynamically regulate the hydrophilicity and charge distribution on the surface of sludge particles, forming a hydrophobic barrier and reducing secondary water adsorption. Compared with traditional conditioning agents that rely solely on charge neutralization or macromolecular encapsulation, this invention overcomes the problem of high particle moisture stability hindering thorough dewatering, further improving the efficiency and completeness of sludge dewatering.
[0032] 3. The composite conditioner of this invention employs free radical oxidation and multi-scale dispersion technology, combined with a stepwise optimized mixing preparation process, to achieve highly efficient synergy among the multiple components in the conditioner. Existing technologies generally suffer from uneven conditioner composition and large fluctuations in performance. The technical solution of this invention addresses this deficiency through the dynamic release of distributed active components, making sludge conditioning more stable and reliable.
[0033] 4. This invention significantly reduces the mechanical resistance of sludge dewatering and substantially reduces dewatering energy consumption by controlling the ratio range of the conditioning agent and process parameters. Compared with existing mechanical dewatering equipment that relies on high-pressure operation to achieve low moisture content, this invention effectively alleviates mechanical load pressure and avoids problems of excessive equipment energy consumption or high operating costs, providing a more economical solution for large-scale industrial promotion. Detailed Implementation
[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0035] This invention provides a composite conditioner for sludge dewatering. This conditioner not only significantly improves the dewatering efficiency of sludge but also effectively reduces the moisture content of the dewatered sludge, improves the quality of the filtrate, and reduces the energy consumption of mechanical dewatering. The composite conditioner for sludge dewatering provided by this invention mainly consists of the following four core components: Lewis acid metal salt, free radical generator, surfactant, and nano-additives. The following is a detailed description of each component and its specific preparation and application:
[0036] Lewis acid metal salts:
[0037] Lewis acid metal salts are one of the core components of the conditioner in this invention, primarily used to alter the chemical properties of the sludge particle surface. Through the coordination of Lewis acids with the carboxyl and hydroxyl groups on the sludge particle surface, the polar bonds on the particle surface are broken, thereby releasing bound water. Preferred Lewis acid metal salts in this invention include titanates, vanadates, and molybdates, such as titanium tetrachloride (TiCl4), sodium metavanadate (NaVO3), and sodium metamolybdate (Na2MoO4).
[0038] In the preparation of the conditioner, Lewis acid metal salts are first dissolved in deionized water to form a 20%–40% solution. The pH of the solution is then adjusted to 6.5–7.5 by adding an alkaline adjuster (such as NaOH) to optimize its coordination activity. The stirring time is controlled at 10–20 minutes, and the stirring speed is 300–500 rpm to ensure the solution is homogeneous.
[0039] Free radical generating agents:
[0040] Free radical generating agents are used to provide strong oxidizing free radicals, such as sulfate radicals (SO4· ... - This process further weakens the stability between sludge particles by oxidizing and degrading the organic colloidal layer on the surface of the sludge particles. Preferred free radical generating agents of this invention include sodium persulfate (Na2S2O8) and ammonium persulfate ((NH4)2S2O8).
[0041] During preparation, the free radical generating agent is dissolved in deionized water at a mass concentration of 5%–10%, with the dissolution temperature maintained at 20℃–25℃ and the stirring speed at 200 rpm–400 rpm until completely dissolved. The prepared free radical solution must be stored away from light to prevent premature decomposition of the free radical generating agent.
[0042] Surfactants:
[0043] Surfactants reduce the surface tension between sludge particles and form a hydrophobic barrier on the particle surface by altering the physicochemical properties of the particle surface. The preferred surfactants in this invention are amphoteric surfactants, such as sulfobetaine or alkylobetaine.
[0044] In the preparation of the conditioner, the surfactant is dissolved in warm water (30℃~50℃) at a mass concentration of 5%~15%, with a stirring speed of 400rpm~600rpm and a stirring time of 5 minutes~10 minutes until completely dissolved. The resulting solution is clear and transparent, without undissolved particles, and the surfactant's performance can be fully utilized in the subsequent sludge conditioning process.
[0045] Nano-additives:
[0046] Nanoparticle additives, through their high specific surface area and catalytic properties, enhance the modification effect of conditioners on sludge particles, while simultaneously forming a microstructural barrier to inhibit the reabsorption of water by the sludge particles. Preferred nanoparticle additives in this invention include zinc oxide (ZnO) and titanium dioxide (TiO2), with particle sizes controlled between 10 nm and 100 nm.
[0047] In the preparation of the conditioner, the nano-adjuvants are added to deionized water at a ratio of 1‰ to 5‰ and dispersed for 10 to 20 minutes using an ultrasonic disperser (power 100W to 200W, frequency 20kHz to 40kHz) until a stable suspension is formed. Ultrasonic treatment can effectively break the aggregation of nanoparticles and ensure their uniform distribution in the conditioner.
[0048] Preparation of mixed conditioners:
[0049] The prepared Lewis acid metal salt solution, free radical generating agent solution, surfactant solution, and nano-auxiliary agent suspension were mixed in a certain ratio, ranging from 3:1:1:1 (mass ratio). During the mixing process, the stirring speed was controlled at 400 rpm to 600 rpm, and the stirring time was 10 to 15 minutes, until a uniform emulsion-like composite conditioner was formed.
[0050] The resulting compound conditioner has a pH value controlled at 6-7 and can be stored stably at room temperature for 6-12 months without stratification or performance changes.
[0051] Sludge conditioning and dewatering processes:
[0052] The sludge dewatering composite conditioner provided by this invention is widely applicable to various types of sludge, including municipal sludge, industrial sludge, high-oil-content sludge, and high-viscosity sludge. The following is a typical sludge conditioning and dewatering process flow:
[0053] Conditioner addition:
[0054] The conditioner is added to the sludge at a ratio of 5‰ to 10‰ of the wet weight of the sludge. The amount added can be adjusted according to the type of sludge and the treatment objectives.
[0055] Stirring reaction:
[0056] Stir for 35 minutes using a low-speed mixer (50 rpm to 100 rpm) to ensure the conditioner is evenly distributed on the surface of the sludge particles, thereby enhancing the reaction and flocculation effect between particles.
[0057] Static reaction:
[0058] The settling time is 5 to 15 minutes to allow the conditioner to fully react with the sludge particles, and the formation of sludge flocs and water separation are observed.
[0059] Mechanical dehydration:
[0060] The conditioned sludge is fed into mechanical dewatering equipment (such as a belt filter press or centrifugal dewatering machine) for dewatering under operating pressures of 0.3 MPa to 0.6 MPa or speeds of 1500 rpm to 2000 rpm. The final sludge moisture content can be reduced to 40% to 45%.
[0061] To further verify the performance of the sludge dewatering composite conditioner of this invention and its applicability under different sludge types and treatment conditions, multiple sets of experimental examples and comparative experiments were conducted. Through optimization of the conditioner formulation, adjustment of dosage, and testing of different sludge characteristics, the experiments compared and analyzed the differences between the conditioner of this invention and existing technologies in terms of dewatering efficiency, filtrate quality, and sludge flocculation, fully demonstrating the technical advantages and practical application effects of this invention. The following is a detailed description of each experimental example.
[0062] Example 1: Conditioning and Dewatering of Municipal Sludge
[0063] Conditioner preparation:
[0064] Take 50g of titanium tetrachloride (TiCl4), dissolve it in deionized water, and prepare a Lewis acid solution with a mass concentration of 30%.
[0065] Adjust the pH of the solution to 7, add NaOH solution dropwise while stirring for 15 minutes at a stirring speed of 400 rpm;
[0066] Take another 15g of sodium persulfate, dissolve it in 300mL of deionized water, let it stand for 30 minutes to decompose, and set aside for later use;
[0067] Dissolve 10g of sulfobetaine in warm water at 50℃ and stir continuously until completely dissolved at a stirring speed of 500rpm.
[0068] 2g of nano zinc oxide was ultrasonically dispersed in 100mL of deionized water under the following conditions: power 150W, frequency 25kHz, and dispersion time 15 minutes.
[0069] Finally, the four solutions were mixed in a ratio of 3:1:1:1 and stirred for 10 minutes to obtain a compound conditioning emulsion.
[0070] Sludge conditioning:
[0071] Take 100 kg of municipal sludge (initial moisture content 78%), add 1 kg of compound conditioner, and add it evenly at a ratio of 5‰.
[0072] Use a mixing device at 60 rpm for 3 minutes to ensure the conditioner is evenly distributed.
[0073] After standing for 10 minutes, the sludge particles gradually flocculated into clumps, and water was observed to be released between the particles, showing obvious sedimentation and stratification.
[0074] Mechanical dehydration:
[0075] The conditioned sludge was fed into a belt filter press, with the operating pressure set at 0.4 MPa. After filtration, the sludge moisture content decreased from 78% to 42.5%. The suspended solids concentration in the filtrate was controlled below 150 mg / L, with no obvious particle deposition.
[0076] Example 2: Deep dewatering of industrial sludge
[0077] Conditioner preparation:
[0078] Weigh out 30g of sodium metavanadate (NaVO3), dissolve it in deionized water to prepare a 25% solution, and adjust the pH of the solution to 6.8;
[0079] Dissolve 20g of sodium persulfate in 500mL of deionized water and let stand at room temperature until completely dissolved;
[0080] Take another 10g of alkyl betaine, dissolve it in warm water (45℃), stir for 5 minutes until the solution is clear;
[0081] Dissolve 3g of nano-titanium dioxide particles (TiO2, 20nm) in 300mL of deionized water and ultrasonically disperse for 12 minutes at a power of 120W.
[0082] Mix the above solutions in a ratio of 4:2:1:1 and stir for 8 minutes to obtain the compound conditioner.
[0083] Sludge conditioning:
[0084] The compound conditioner was added to 200 kg of industrial sludge (initial moisture content 80%) at a ratio of 6‰. The mixture was stirred at 80 rpm for 4 minutes. After standing for 15 minutes, large flocs appeared in the sludge particles, colloidal water was gradually released, the sludge layer volume decreased, and surface moisture was clearly precipitated.
[0085] Mechanical dehydration:
[0086] The conditioned sludge is fed into a centrifugal dewatering machine, with the speed set at 1800 rpm. After dewatering, the sludge moisture content is reduced to 40.8%, and the organic matter concentration in the filtrate is controlled below 200 mg / L, meeting the industrial sludge discharge standards.
[0087] Example 3: Treatment of High-Viscosity Sludge
[0088] Conditioner preparation:
[0089] Dissolve 60g of titanium tetrachloride (TiCl4) in 400mL of deionized water to prepare a 35% solution.
[0090] Add NaOH to adjust the pH of the solution to 7.2, stir for 20 minutes at a speed of 500 rpm.
[0091] Weigh 10g of ammonium persulfate ((NH4)2S2O8) and dissolve it in 200mL of water. After dissolving, seal and store.
[0092] Dissolve 15g of sulfobetaine in hot water (50℃) while stirring at 600rpm. After complete dissolution, cool and set aside.
[0093] 5g of nano zinc oxide particles were ultrasonically dispersed in 200mL of deionized water under ultrasonic conditions of 200W for 18 minutes.
[0094] Mix the above solution in a ratio of 3:1:2:1 and stir at low speed for 10 minutes to complete the conditioning agent.
[0095] Sludge conditioning:
[0096] 100 kg of high-viscosity sludge (initial moisture content 82%) was mixed with 1.5 kg of conditioning agent. The mixing equipment was set to 50 rpm and stirred for 4 minutes, at which point the sludge began to separate into layers. After standing for 12 minutes, the flocs further increased in size, and the sludge viscosity decreased significantly.
[0097] Mechanical dehydration:
[0098] The conditioned sludge was fed into a filter press with a pressure set at 0.6 MPa. After dewatering, the sludge moisture content dropped to 43%, the filtration time was shortened by 30%, and the suspended solids content in the filtrate remained stable below 120 mg / L.
[0099] Example 4: Dewatering of high-oil-content sludge
[0100] Conditioner preparation:
[0101] Dissolve 40g of sodium metamolybdate (Na2MoO4) in 300mL of deionized water, add a small amount of NaOH to adjust the pH to 6.9, and stir for 15 minutes;
[0102] Dissolve 15g of sodium persulfate in 400mL of water and let it stand to decompose;
[0103] Dissolve 12g of sulfobetaine in hot water (40℃) and stir until completely dissolved;
[0104] 2g of nano-titanium dioxide (TiO2) particles were ultrasonically dispersed for 12 minutes at a power of 150W.
[0105] Mix the components in a ratio of 5:2:2:1 and stir for 5 minutes to obtain the final product.
[0106] Sludge conditioning:
[0107] 150 kg of oily sludge (85% moisture content) was mixed with a conditioner at a ratio of 8‰. The mixture was stirred at low speed for 3 minutes, and the sludge particles quickly agglomerated. After a 10-minute settling time, oil-water separation was observed.
[0108] Mechanical dehydration:
[0109] The oily sludge was dewatered using a centrifuge at a speed of 2000 rpm. After dewatering, the sludge moisture content was reduced to 45.5%, and the oil content in the filtrate was reduced to below 150 mg / L.
[0110] Example 5: High-efficiency application of compound conditioners
[0111] Conditioner preparation:
[0112] 50g of titanium tetrachloride and 10g of sodium persulfate were dissolved separately and stored independently. Sulfobetaine and nano-zinc oxide were prepared using conventional methods. Finally, they were mixed in a 4:1:2:1 ratio and stirred for 12 minutes to obtain a highly uniform emulsion.
[0113] Sludge conditioning:
[0114] Sludge (200 kg, moisture content 78%), added at a ratio of 7‰. After stirring for 3 minutes, let stand for 15 minutes. Observe that the sludge particles increase significantly, the bound water is released significantly, and a dense sludge layer is formed.
[0115] Mechanical dehydration:
[0116] The filter press operates at a pressure of 0.5 MPa, and the moisture content of the sludge after dewatering is reduced to 41.5%, shortening the operation time by 20% compared to conventional methods.
[0117] To further verify the function and synergistic effect of each component of this invention, multiple comparative experiments were conducted. By comparing comparative examples lacking core components or key parameter adjustments with examples of the complete formulation, the core innovations of this invention's conditioning agent and the shortcomings of existing technologies can be clearly revealed. The detailed setup and explanation of the comparative examples are as follows:
[0118] Comparative Example 1 (corresponding to Example 1): No Lewis acid metal salts were used.
[0119] Conditioner preparation:
[0120] Dissolve 15g of sodium persulfate in 300mL of deionized water until completely dissolved, then set aside for later use.
[0121] Dissolve 10g of sulfobetaine in warm water at 45℃, stirring at 500rpm until completely dissolved;
[0122] 2g of nano zinc oxide was ultrasonically dispersed in 200mL of deionized water at an ultrasonic power of 150W for 15 minutes.
[0123] The three solutions were mixed in a 3:1:1 ratio and stirred for 10 minutes to obtain the conditioning agent solution. No Lewis acid metal salt components were added.
[0124] Sludge conditioning:
[0125] 1 kg of conditioner was added to 100 kg of municipal sludge (initial moisture content 78%), and the stirring equipment was set to 60 rpm for 3 minutes. After standing for 10 minutes, the sludge particles began to flocculate, but there was no obvious stratification.
[0126] Mechanical dehydration:
[0127] The conditioned sludge is fed into a belt filter press for dewatering, with the operating pressure set at 0.4 MPa.
[0128] Comparative Example 2 (corresponding to Example 2): No free radical generating agent used
[0129] Conditioner preparation:
[0130] Dissolve 30g of sodium metavanadate (NaVO3) in 300mL of deionized water, adjust the pH to 6.8, and adjust it dropwise with NaOH solution while stirring at 400rpm for 15 minutes.
[0131] Dissolve 10g of sulfobetaine in warm water at 50℃, stirring at 500rpm;
[0132] 3g of nano-titanium dioxide particles were ultrasonically dispersed in 300mL of deionized water for 12 minutes.
[0133] The three solutions were mixed in a 4:1:1 ratio and stirred for 8 minutes to obtain a conditioning emulsion. No free radical generating agent components were added.
[0134] Sludge conditioning:
[0135] Take 200 kg of industrial sludge (initial moisture content 80%) and add 1.2 kg of conditioner (dosage ratio 6‰). Stir at 80 rpm for 4 minutes. Let stand for 15 minutes and observe the formation of sludge flocs.
[0136] Mechanical dehydration:
[0137] The conditioned sludge is fed into a centrifugal dewatering machine, with the operating speed set at 1800 rpm.
[0138] Comparative Example 3 (corresponding to Example 3): No surfactant used
[0139] Conditioner preparation:
[0140] Dissolve 60g of titanium tetrachloride (TiCl4) in deionized water to prepare a 35% solution. Adjust the pH of the solution to 7.2 with NaOH and stir for 20 minutes at a speed of 500 rpm.
[0141] Dissolve 10g of ammonium persulfate in 200mL of water and let stand for later use. Disperse 5g of nano-zinc oxide particles ultrasonically in 200mL of deionized water at 200W for 18 minutes.
[0142] Mix the above solutions in a 3:1:1 ratio and stir at low speed for 10 minutes to obtain a conditioning emulsion.
[0143] No sulfobetaine or other surfactants were added.
[0144] Sludge conditioning:
[0145] 100 kg of high-viscosity sludge (initial moisture content 82%) was mixed with 1.5 kg of conditioning agent. The stirring equipment was set to 50 rpm and stirred for 4 minutes, then allowed to stand for 12 minutes.
[0146] Mechanical dehydration:
[0147] The conditioned sludge is fed into a filter press, with the operating pressure set at 0.6 MPa.
[0148] Comparative Example 4 (corresponding to Example 4): No nanoparticle additives used
[0149] Conditioner preparation:
[0150] Dissolve 40g of sodium metamolybdate (Na2MoO4) in 300mL of deionized water, adjust the pH to 6.9, stir at 400rpm for 15 minutes;
[0151] Dissolve 15g of sodium persulfate in 400mL of deionized water and let it stand to decompose for later use;
[0152] Dissolve 12g of sulfobetaine in warm water at 45℃ with a stirring speed of 500rpm until completely dissolved and set aside.
[0153] Mix the solutions in a 5:2:2 ratio and stir for 5 minutes to obtain the conditioning emulsion;
[0154] No nano zinc oxide or other nanoparticle additives were added.
[0155] Sludge conditioning:
[0156] 150 kg of oily sludge (initial moisture content 85%), add conditioner at a ratio of 8‰, stir at low speed for 3 minutes, and let stand for 10 minutes.
[0157] Mechanical dehydration:
[0158] The oily sludge is dewatered by a centrifuge with a speed of 2000 rpm.
[0159] Comparative Example 5 (corresponding to Example 5): Lewis acid metal salt concentration decreased
[0160] Conditioner preparation:
[0161] 25g of titanium tetrachloride (TiCl4) was dissolved in 300mL of deionized water to prepare a 15% (w / w) solution.
[0162] Adjust the pH of the solution to 7.1 with NaOH, stir for 15 minutes at a speed of 400 rpm;
[0163] Dissolve 10g of sodium persulfate in 300mL of water and let stand for later use;
[0164] Sulfobetaine was prepared using conventional methods at a concentration of 10%. Nano-zinc oxide was ultrasonically dispersed at a ratio of 2‰ with a power of 150W. The four solutions were mixed in a ratio of 4:1:2:1 and stirred for 12 minutes. The Lewis acid concentration was reduced by 50% compared to that in Example 5.
[0165] Sludge conditioning:
[0166] Add 200 kg of sludge and conditioner at a ratio of 7‰. Stir at 60 rpm for 3 minutes and let stand for 15 minutes.
[0167] Mechanical dehydration:
[0168] The sludge is dewatered by a belt filter press with an operating pressure of 0.5 MPa.
[0169] Comparative Example 6 (corresponding to Example 2): pH value not adjusted
[0170] Conditioner preparation:
[0171] Dissolve 30g of sodium metavanadate (NaVO3) in 300mL of deionized water and use the solution directly without pH adjustment (pH approximately 5.2).
[0172] Dissolve 15g of sodium persulfate in 500mL of water and let it stand before use;
[0173] Dissolve 10g of sulfobetaine in 50℃ warm water and stir until completely dissolved;
[0174] 3g of nano zinc oxide particles were ultrasonically dispersed at 120W for 12 minutes.
[0175] Mix the above solutions in a 3:1:1:1 ratio and stir for 8 minutes to complete the conditioning agent.
[0176] Sludge conditioning:
[0177] 200 kg of industrial sludge, add 1.2 kg of conditioner, stir for 4 minutes, and let stand for 15 minutes.
[0178] Mechanical dehydration:
[0179] The industrial sludge is processed by a centrifugal dewatering machine with an operating speed of 1800 rpm.
[0180] To comprehensively verify the effectiveness of the sludge dewatering composite conditioner of this invention and highlight its advantages over existing technologies, multiple comparative experiments and examples were designed for comparison. Through the comparative experiments, the effects of missing single components or parameter adjustments on dewatering performance and filtrate quality were analyzed, further demonstrating the inventiveness of the conditioner in terms of component synergy, process optimization, and application performance. The following are the comparative experimental contents of specific examples and comparative examples.
[0181] Experiment 1: Comparison of sludge dewatering rates
[0182] Experimental subjects:
[0183] This experiment used municipal sludge with an initial moisture content of 78% and a total sludge mass of 100 kg. The sludge was generated during the treatment of domestic sewage and had a high content of bound water and colloidal water, requiring dewatering through chemical conditioning and mechanical pressure filtration.
[0184] Experimental sample setup:
[0185] Example 1: The compound conditioner contains titanium tetrachloride (TiCl4), sodium persulfate, sulfobetaine and nano zinc oxide.
[0186] Comparative Example 1: Conditioner without Lewis acid metal salts.
[0187] Comparative Example 3: Conditioner without surfactants.
[0188] Comparative Example 4: Conditioner without nano zinc oxide.
[0189] Experimental steps:
[0190] Prepare the conditioner according to the conditioner formula in the experimental protocol, and stir well;
[0191] Each group of sludge was given a corresponding conditioner at a ratio of 5‰ (based on the mass of wet sludge).
[0192] Stir for 3 minutes using a low-speed mixer (60 rpm) to ensure that the conditioner is in full contact with the sludge;
[0193] After standing for 10 minutes, the sludge enters the belt filter press. The filter press operates at a pressure of 0.4 MPa.
[0194] Record the moisture content of the dewatered sludge and determine the residual moisture by weighing. Each experiment was repeated three times, and the average value was taken.
[0195] Experimental data table:
[0196] Table 1: Experimental data on the effect of different conditioners on sludge dewatering:
[0197]
[0198] Experiment Summary:
[0199] After dehydration, the sludge moisture content of Example 1 was significantly lower than that of the comparative group, reflecting the superiority of the conditioner of the present invention. Through the action of the Lewis acid metal salt in the conditioner, the polar bonds on the surface of the sludge particles broke, releasing a large amount of bound water. In contrast, Comparative Example 1, lacking Lewis acids, maintained the intact polar characteristics of the sludge particles, resulting in insufficient release of bound water and a high moisture content. Conditioners with only flocculation effects are insufficient to completely solve the problem of strongly bound water.
[0200] The absence of surfactant (Comparative Example 3) also showed a significant disadvantage. The introduction of surfactant, by reducing the surface tension of sludge particles, strengthens the formation of hydrophobic barriers and reduces the secondary adsorption of water on the particle surface. In Comparative Example 3, the residual water content between particles was higher, the hydrolysis between particles was insufficient, and the final moisture content after dewatering was relatively high.
[0201] The synergistic effect of nanoparticle additives is equally crucial. Comparative Example 4 data shows that the dewatering efficiency of sludge significantly decreased in the absence of nano-zinc oxide. This is because nanoparticles not only provide additional active sites for chemical reactions but also further enhance water separation between particles through a microstructural barrier effect. In Example 1, the presence of nano-additives optimized the entire dewatering process, enabling the sludge to achieve good results even under lower mechanical pressure.
[0202] Experiment 2: Comparative Experiment on the Flocculation Properties of Sludge Particles
[0203] Experimental subjects:
[0204] This experiment used industrial sludge with an initial moisture content of 80% and a total sludge mass of 200 kg. The sludge originated from a chemical plant and was characterized by its small particle size, negative charge, and high stability. Before dewatering, it needed to be flocculated to modify its particle characteristics.
[0205] Experimental sample setup:
[0206] Example 2: The compound conditioner contains sodium metavanadate (NaVO3), sodium persulfate, sulfobetaine and nano titanium dioxide.
[0207] Comparative Example 2: The conditioner does not contain free radical generating agents.
[0208] Comparative Example 6: The conditioner did not adjust the pH value.
[0209] Experimental steps:
[0210] Conditioner addition: Add the conditioner to the sludge sample at a ratio of 6‰ of the wet weight of the sludge to ensure that the conditioner configuration used in different groups meets the design requirements;
[0211] Stirring reaction: Stir at 80 rpm for 4 minutes using a stirring device to ensure that the conditioner is fully dispersed and in contact with the sludge;
[0212] Settling: Allow the reaction to stand for 15 minutes, observe the sludge flocculation state, and record the formation of visible sludge flocs;
[0213] Particle size determination: Take a sludge sample after it has been allowed to stand, and use a laser particle size analyzer to measure the particle size distribution of the flocs and record the average particle size.
[0214] Floc strength determination: The sludge sample was centrifuged at low speed (1000 rpm), and the particle size change of the flocs under centrifugal force was measured to calculate the floc strength.
[0215] Experimental data recording:
[0216] Record the average particle size and particle size variation of the flocs for each group of samples. Repeat the experiment three times and take the average value.
[0217] Experimental data table:
[0218] Table 2: Experimental data on the effects of different conditioners on sludge flocculation:
[0219]
[0220] Experiment Summary:
[0221] Example 2 demonstrated superior flocculation, with floc particle size significantly larger than Comparative Examples 2 and 6. The free radical generator played a crucial role in this process. Sulfate free radicals generated from the decomposition of sodium persulfate oxidized and degraded the organic colloidal layer on the surface of the sludge particles, weakening the electrostatic repulsion between particles and thus promoting particle aggregation into larger flocs. In Comparative Example 2, the lack of synergistic effect from free radicals limited floc formation, and the colloidal stability between particles remained high, resulting in a significantly smaller particle size.
[0222] Comparative Example 6, without pH adjustment, also revealed deficiencies. Under slightly acidic conditions (pH≈5.2), the coordination activity of Lewis acid metal salts decreased, vanadates could not effectively bind to polar groups on the sludge surface, the surface modification of particles was inhibited, and the flocculation process was affected. At the same time, the decomposition rate of free radical generators in slightly acidic environments was unstable, resulting in insufficient overall activity of the conditioner.
[0223] In the experiment, the floc particle size of Example 2 maintained high stability under centrifugal force, with a particle size change of only 14.2%. This phenomenon indicates that the conditioner, through the introduction of surfactants and nanoparticle additives, improved the mechanical strength and structural integrity of the flocs. In contrast, the flocs of Comparative Examples 2 and 6 showed a significant decrease in particle size under centrifugal force, indicating that their floc structure was relatively loose and lacked stability. This further demonstrates the advantages of the conditioner in Example 2 in terms of particle surface reaction and flocculation enhancement.
[0224] Experiment 3: Comparison of Filtrate Mass
[0225] Experimental subjects:
[0226] This experiment used high-viscosity sludge with an initial moisture content of 82% and a total sludge mass of 100 kg. The sludge originated from a food processing plant wastewater treatment system and had a high content of colloidal organic matter and flocculation stability, resulting in a high concentration of suspended solids in the filtrate.
[0227] Experimental sample setup:
[0228] Example 3: The conditioner consists of titanium tetrachloride (TiCl4), ammonium persulfate, sulfobetaine and nano zinc oxide.
[0229] Comparative Example 1: The conditioner does not contain Lewis acid metal salts.
[0230] Comparative Example 4: The conditioner does not contain nano zinc oxide.
[0231] Experimental steps:
[0232] Conditioner preparation: Prepare the corresponding reagents according to the formula of each conditioner group, ensuring that they are fully dissolved and stirred evenly;
[0233] Conditioner addition: Each group of conditioners is added to the high-viscosity sludge sample at a ratio of 1.5‰ of the wet weight of the sludge;
[0234] Stirring reaction: Stir the sludge and conditioner in a low-speed mixer at 50 rpm for 4 minutes;
[0235] Static reaction: Let stand for 12 minutes and observe the separation of sludge particles and the transparency of the upper filtrate;
[0236] Mechanical dewatering: The conditioned sludge sample is fed into a filter press, the operating pressure is set to 0.6 MPa, and the filtrate is collected for analysis;
[0237] Filtrate quality determination: Take a filtrate sample, filter it with filter paper, and measure the mass of the residue on the filter paper. The filtrate quality is characterized by the suspended solids concentration (mg / L).
[0238] Experimental data recording:
[0239] Record the suspended solids concentration of each group of filtrates. Repeat the experiment three times and take the average value.
[0240] Experimental data table:
[0241] Table 3: Experimental data on the effect of different conditioning agents on the concentration of suspended solids in the filtrate:
[0242]
[0243] Experiment Summary:
[0244] Example 3 demonstrated excellent filtrate quality, with a significantly lower suspended solids concentration than the comparative group. This was attributed to the synergistic effect of the Lewis acid metal salt and the free radical generator in the conditioner. Titanium tetrachloride, by coordinating with the carboxyl and hydroxyl groups on the surface of sludge particles, disrupted their polar structure, loosening the colloidal and bound water between particles. The released fine particles were then captured by the flocculant rather than entering the filtrate. In Comparative Example 1, lacking the Lewis acid metal salt, the polar bound water on the surface of the sludge particles was not fully released, making it easier for fine particles to remain in the filtrate, resulting in a higher suspended solids concentration.
[0245] The introduction of nanoparticle additives significantly enhanced the overall performance of the conditioner. In Example 3, nano-zinc oxide not only accelerated the aggregation of sludge particles through catalytic surface reactions but also reduced the risk of particle redispersion in the filtrate through a microstructural barrier effect. In Comparative Example 4, the lack of nano-zinc oxide resulted in improved sludge dewatering, but the suspended solids concentration in the filtrate remained high. This demonstrates that nano-additives play an indispensable role in improving filtrate quality.
[0246] Furthermore, the oxidation effect of the free radical generating agent plays a crucial role throughout the process. In Example 3, the sulfate free radicals released by ammonium persulfate not only degraded the organic colloidal components in the sludge but also further disrupted the stability of the particles, providing a more effective opportunity for the surfactant and flocculant to act. Data from Comparative Example 1 verified that without this process, the sludge conditioner's action depth was significantly insufficient, ultimately leading to higher levels of pollutants in the filtrate. This series of mechanisms combined resulted in the filtrate quality of Example 3 being superior to other groups, especially in achieving more ideal results in controlling suspended solids concentration.
[0247] Experiment 4: Comparative Experiment on Dewatering Effect of High Oil Content Sludge
[0248] Experimental subjects:
[0249] This experiment used high-oil-content sludge with an initial moisture content of 85% and a total sludge mass of 150 kg, sourced from a petrochemical wastewater treatment plant. The sludge contained a large amount of oily substances, exhibited strong hydrophobicity on its surface, and had high particle stability, making it difficult for conventional conditioning agents to effectively dehydrate it.
[0250] Experimental sample setup
[0251] Example 4: The conditioner is composed of sodium metamolybdate (Na2MoO4), sodium persulfate, sulfobetaine and nano titanium dioxide.
[0252] Comparative Example 4: The conditioner does not contain nanoparticle additives.
[0253] Comparative Example 5: The concentration of Lewis acid metal salt was halved (compared to Example 4).
[0254] Experimental steps:
[0255] Conditioner addition: Add the corresponding conditioner to the sludge at a ratio of 8‰ of the wet weight of the sludge;
[0256] Stirring reaction: Use a low-speed stirring device with a speed set at 60 rpm and a stirring time of 3 minutes to ensure that the conditioner and sludge are in full contact.
[0257] Static reaction: After standing for 10 minutes, observe the oil-water separation phenomenon and record the oil droplet precipitation.
[0258] Mechanical dewatering: The conditioned sludge is fed into a centrifugal dewatering machine, which is run at 2000 rpm. The moisture content of the sludge after dewatering is recorded.
[0259] Determination of oil content in filtrate: Collect the dehydrated filtrate and use an oil analyzer to determine the oil content (mg / L) in the filtrate to characterize the oil-water separation effect.
[0260] Experimental data recording
[0261] Each experiment was repeated 3 times, and the moisture content of the sludge after dewatering and the oil content of the filtrate were recorded.
[0262] Experimental Data Table
[0263] Table 4: Experimental data on the dewatering effect of different conditioners on high-oil-content sludge:
[0264]
[0265] Experiment Summary:
[0266] Example 4 demonstrates outstanding performance in treating high-oil-content sludge. The nanoparticle additive plays a crucial role. Nano-titanium dioxide provides numerous active sites, not only enhancing the effect of the conditioner on the sludge particle surface but also forming a stable microstructural barrier that effectively inhibits the recombination of oil and water molecules. In Comparative Example 4, lacking the nanoparticle additive, although destabilization and aggregation between sludge particles still exist, the loose particle structure leads to a significant decrease in oil-water separation efficiency and a higher oil content in the filtrate. This demonstrates the critical role of nanoparticles in the dewatering of high-oil-content sludge.
[0267] For Comparative Example 5, the reduced concentration of Lewis acid metal salts resulted in better performance than Comparative Example 4, but still inferior to Example 4. This phenomenon clearly demonstrates that Lewis acid metal salts, through coordination, alter the chemical properties of the sludge particle surface, disrupting the binding force between oil and sludge particles. Reducing the Lewis acid concentration weakened the effect of this modification, and the destabilization of the particles was also affected, manifested as a higher oil content in the filtrate and a less than ideal moisture content after sludge dewatering.
[0268] The role of free radical generators cannot be ignored. In Example 4, sulfate free radicals degraded the organic protective layer on the surface of sludge particles through strong oxidation, providing greater room for the action of Lewis acids and surfactants. In Comparative Example 5, although free radical generators were still present, the synergistic effect of the entire conditioning process was weakened due to insufficient Lewis acid concentration. This imbalance is directly reflected in the dewatering efficiency and filtrate oil content; compared with Example 4, the dewatered sludge had a slightly higher moisture content and the filtrate oil content was also higher. Based on the above observations, the overall technical solution of Example 4 is more able to meet the treatment needs of high-oil-content sludge.
[0269] Experiment 5: Effect of Conditioner Dosage on Sludge Dewatering Efficiency
[0270] Experimental subjects:
[0271] This experiment used municipal sludge with an initial moisture content of 78% and a total sludge mass of 100 kg. The sludge originated from the primary sedimentation tank of a municipal wastewater treatment plant. This type of sludge has fine particles and a high content of bound water and colloidal water; therefore, its dewatering efficiency is closely related to the amount of conditioner used.
[0272] Experimental sample setup:
[0273] Example 1: The compound conditioner was used to treat sludge at dosages of 5‰, 7‰ and 10‰.
[0274] Comparative Example 1: The conditioner does not contain Lewis acid metal salts, and the dosage is fixed at 7‰.
[0275] Experimental steps:
[0276] Conditioner addition: Add each group of conditioners to 100kg of municipal sludge according to the designed ratio, ensuring that the dosage and formula of different groups are consistent;
[0277] Stirring reaction: Stir at 60 rpm for 3 minutes using a stirring device to evenly disperse the conditioning agent;
[0278] Static reaction: After standing for 10 minutes, observe the separation of sludge particles and the state of liquid phase precipitation;
[0279] Mechanical dewatering: The conditioned sludge sample was fed into a belt filter press, with the operating pressure set to 0.4 MPa. The moisture content of the dewatered sludge was recorded, and the filtration time was measured.
[0280] Experimental data recording:
[0281] Record the moisture content and filtration time of the sludge after dewatering in each group. The experiment was repeated 3 times and the average value was taken.
[0282] Experimental data table:
[0283] Table 5: Experimental data on the effect of conditioner dosage on sludge dewatering:
[0284]
[0285] Experiment Summary:
[0286] The dosage of conditioner directly affects the sludge dewatering effect. In Example 1, the moisture content and filtration time under different dosages showed a regularity. When the dosage was 5‰, the moisture content of the dewatered sludge was 47.8%, and the filtration time was relatively long. As the dosage increased to 7‰, the moisture content decreased to 42.5%, and the filtration time shortened to 18.7 minutes. When further increased to 10‰, the moisture content of the sludge further decreased to 40.2%, but the improvement in effect tended to plateau. This indicates that within a certain range, the higher the dosage of conditioner, the better the efficiency of releasing bound water. However, beyond the optimal dosage, the synergistic effect of the conditioner gradually weakens, leading to a decrease in economic efficiency.
[0287] The dewatering effect of Comparative Example 1 was significantly inferior to that of Example 1, which fully demonstrates the important role of Lewis acid metal salts. Lewis acids disrupt the polar groups on the surface of sludge particles through coordination, thereby releasing strongly bound water. In Comparative Example 1, due to the lack of Lewis acid metal salts, the surface structure of the sludge particles remained intact, resulting in a significant reduction in the removal efficiency of bound water. Increasing the amount of conditioner had limited effect on improving the effect of Comparative Example 1, indicating that relying solely on flocculation and surfactants is insufficient to achieve a significant improvement in dewatering efficiency.
[0288] Mechanistically, the synergistic effect of free radical generators and nano-adjuvants is particularly evident in high-dosage conditioners. Free radicals generated by persulfate reduce the chemical stability of sludge particle surfaces through oxidation, while nano-zinc oxide provides more reaction sites, enhancing particle aggregation. At higher dosages (10‰), this synergistic effect makes the particle structure more stable, significantly reducing resistance to mechanical dewatering. Therefore, Example 1 achieved excellent dewatering results under suitable dosage conditions, while Comparative Example 1 lacked a core modifying component, making it difficult to significantly improve its dewatering efficiency. Based on the experimental results, the optimal dosage of the conditioner is recommended to be 7‰, which achieves both high-efficiency dewatering and good economic benefits.
[0289] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A sludge dewatering composite conditioner, characterized in that, Includes the following components: Lewis acid metal salts; Free radical generating agent; The surfactant is an amphoteric surfactant, specifically sulfobetaine or alkylobetaine; Polymer-type flocculants; Nanoparticle additives; pH adjuster, wherein the pH adjuster is sodium hydroxide or sodium carbonate; The Lewis acid metal salt is a titanate or vanadate, specifically at least one of titanium tetrachloride, sodium metavanadate, and sodium metamolybdate. The free radical generating agent is a persulfate, specifically at least one of sodium persulfate and ammonium persulfate; The polymeric flocculant is cationic polyacrylamide; The nanoparticle additive is zinc oxide or titanium dioxide nanoparticles with a particle size of 10 nm to 100 nm. A method for preparing a sludge dewatering composite conditioner includes the following steps: Lewis acid metal salts are dissolved in deionized water and the pH is adjusted to obtain Lewis acid active solutions. The concentration of the Lewis acid metal salts is 20% to 40%, and the pH adjustment range is 6.5 to 7.
5. A free radical generating agent is dissolved in deionized water to obtain a free radical solution; A surfactant solution is prepared by dissolving the surfactant in deionized water. The nanoparticle additives were dispersed in deionized water by ultrasonication to obtain a nanoparticle additive suspension. Lewis acid active liquid, free radical solution, surfactant solution, nanoparticle auxiliary agent suspension and flocculant are mixed sequentially and stirred evenly to prepare sludge dewatering composite conditioner. The nanoparticle auxiliary agent is ultrasonically dispersed at a power of 100W to 200W, a frequency of 20kHz to 40kHz, and an ultrasonic time of 10 minutes to 20 minutes.
Citation Information
Patent Citations
Sludge deep dehydration composite conditioner and its application
CN103819072A
High-efficiency sludge dehydrating agent
CN107746171A
Chemical conditioning deep dehydration method for sludge
CN114804570A
Nano highly effective amendment for sludge dehydration
CN1621370A
Powdery organic coagulant
JP2014184406A
